Glass fiber composition and glass fiber suitable for large wind turbine blades

By adjusting the glass components and adding specific oxides, the glass network structure is improved and the crystallization activation energy is increased, which solves the problem of strong crystallization ability of the existing glass fiber composition and realizes a glass fiber combination with low density and high elastic modulus. It is suitable for large-scale offshore wind turbine blades and large-scale tank kiln production.

CN118420234BActive Publication Date: 2025-01-21TAISHAN FIBERGLASS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410616701.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-01-21
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

When used in large offshore wind blades, the existing low-density high-modulus glass fiber compositions have strong crystallization capabilities and large crystallization particles, which are difficult to meet the requirements of large-scale pool kiln production.

Method used

By adjusting the glass composition, adding ZnO, Li2O, B2O and other elements, adjusting the ratio of bridging oxygen to non-bridging oxygen, improving the glass network structure, increasing the glass elastic modulus, and increasing the crystallization tendency of zinc-aluminum spinel and quartz by introducing ZnO , causing the glass composition to deviate from the cordierite main phase region in the MgO-Al2O3-SiO2 ternary phase diagram, increasing the crystallization activation energy and reducing the crystallization ability.

Benefits of technology

It achieves low density (≤2.61g/cm3) and high elastic modulus (≥98.7GPa) of the glass fiber composition, while reducing the formation of crystallized particles, and is suitable for large-scale tank kiln production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention belongs to the field of glass fiber technology, and specifically relates to a glass fiber composition and glass fiber suitable for large wind turbine blades. The glass fiber composition, in terms of mass percentage, has the following components: SiO2: 57-62%, Al2O3: 16-21%, CaO: 0.4-4%, MgO: 13-18%, Fe2O3: 0.3-0.8%, Li2O: 0.1-0.7%, Y2O3: 0-2.5%, ZnO: 0.1-4.0%, B2O3: 0.3-0.8%, CeO2: 0.1-0.5%, K2O+Na2O≤0.5%, and the remainder is impurities. The glass fiber composition of the present invention has a low density, and the elastic modulus of the prepared glass fiber is high, which can better meet the requirements of large-scale tank kiln production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass fibers, and in particular relates to a glass fiber composition and glass fibers suitable for large wind turbine blades. Background Art

[0002] With the transformation of the global energy structure and the strengthening of environmental awareness, offshore wind power has become the latest frontier of global wind power development. Compared with onshore wind power, offshore wind power has the characteristics of rich resources, high power generation utilization hours, no land occupation and suitable for large-scale development. In my country, offshore wind power is also regarded as a key area for the development of renewable energy. Therefore, glass fiber is also developing in the direction of ultra-high modulus, low density, excellent fatigue performance and corrosion resistance.

[0003] Low-density glass fiber with ultra-high modulus can effectively reduce the weight of large-scale offshore wind turbine blades, improve power generation efficiency, reduce costs, and further promote the development of offshore wind power.

[0004] Chinese patent CN113929299A discloses a high modulus glass composition, high modulus glass fiber and composite material, which introduces 3-15% rare earth oxide and 0.1-2% ZrO2 to obtain a high modulus glass fiber composition with an elastic modulus of 94-101 GPa. Due to the introduction of a large amount of rare earth oxide and ZrO2, its density is generally greater than 2.66 g / cm 3 , which is not suitable for the needs of large-scale lightweight offshore wind turbine blades.

[0005] Chinese patent CN116282934A discloses a high-magnesium high-specific modulus glass fiber composition, which adjusts the ratio of MgO / Al2O3 to obtain a glass fiber with an elastic modulus of 95-98.5 GPa. In large offshore wind turbine blades, this glass fiber composition still cannot replace carbon fiber well.

[0006] At present, the glass fiber components of low-density and high-modulus glass fiber are generally located in the cordierite main phase area or the enstatite main phase area in the MgO-Al2O3-SiO2 ternary phase diagram, and have strong crystallization ability. In the large-scale pool kiln production process, they face a series of problems such as leak plate back-climbing, crystallization particles clogging the leak nozzle, serious leak plate deformation, and short leak plate life.

[0007] In view of the above problems, there is an urgent need to develop a low-density, high-modulus glass fiber composition suitable for large wind turbine blades, which has excellent mechanical properties but weak crystallization ability and small crystallization particles, and is more suitable for large-scale pool kiln production. Summary of the invention

[0008] The purpose of the present invention is to provide a glass fiber composition suitable for large wind turbine blades. The glass fiber composition has low density and high elastic modulus. By adjusting the glass components, adding elements such as ZnO, Li2O, B2O, adjusting the ratio of bridging oxygen to non-bridging oxygen in the glass, improving the glass network structure, and effectively improving the glass elastic modulus, the glass components are deviated from the cordierite main phase region and the enstatite main phase region in the MgO-Al2O3-SiO2 ternary phase diagram, but the crystallization at the high temperature end of the glass is still mainly cordierite, which increases the crystallization activation energy and reduces the glass crystallization ability, so that it can better adapt to the requirements of large-scale pool kiln production. The present invention also provides a glass fiber made of a glass fiber composition suitable for large wind turbine blades.

[0009] The glass fiber composition suitable for large wind turbine blades of the present invention has the following components in percentage by mass:

[0010] SiO2: 57~62%, Al2O3: 16~21%, CaO: 0.4~4%, MgO: 13~18%, Fe2O3: 0.3~0.8%, Li2O: 0.1~0.7%, Y2O3: 0~2.5%, ZnO: 0.1~4.0%, B2O3: 0.3~0.8%, CeO2: 0.1~0.5%, K2O+Na2O≤0.5%, the rest are impurities.

[0011] in:

[0012] The mass percentage of ZnO and Al2O3 satisfies ZnO / Al2O3=0.02~0.35;

[0013] The mass percentage content of Li2O+ZnO and B2O3 satisfies (Li2O+ZnO) / B2O3≥1.0;

[0014] The mass percentage content of CeO2 and Fe2O3 satisfies CeO2 / Fe2O3≥0.3;

[0015] The mass percentage content of Y2O3 and ZnO satisfies Y2O3+ZnO: 1.0~5.0%.

[0016] The density of the glass fiber composite suitable for large wind turbine blades is ≤2.61g / cm 3 .

[0017] The properties of the glass fiber made from the glass fiber composition suitable for large wind turbine blades are as follows:

[0018] The molding temperature of glass fiber is 1280~1330℃.

[0019] The specific modulus of glass fiber is ≥3.80×10 6 m.

[0020] The elastic modulus of glass fiber is ≥98.7GPa.

[0021] The liquidus temperature of glass fiber is ≤1310℃.

[0022] The glass fiber composition suitable for large wind turbine blades of the present invention is made of the following raw materials:

[0023] Quartz powder, calcined kaolin, dolomite, magnesium oxide, colemanite, yttrium oxide, zinc oxide, cerium oxide, spodumene, mirabilite and lithium slag waste. Among them, calcined kaolin introduces sufficient Al2O3 and Fe2O3 at the same time, which effectively reduces the cost of glass fiber composition; the present invention inevitably introduces a small amount of TiO2, and lithium slag waste is used to replace part of spodumene to introduce Li2O, which greatly reduces the cost of raw materials and can utilize solid waste.

[0024] SiO2 is an important glass-forming oxide, which forms a three-dimensional frame structure in the form of connecting the top corners of silicon-oxygen tetrahedrons [SiO4]. The Si-O bond is a polar covalent bond with a strong bond, and the ion and covalent bond each account for 50%. SiO2 can improve the chemical stability and mechanical strength of glass. When the content is high, a higher melting temperature is required, the difficulty of fiberization increases, and even quartz crystallization may be caused. The present invention limits the content range of SiO2 to 57~62%.

[0025] Al2O3 is an intermediate oxide with multiple coordination in the glass network structure. When there is less free oxygen in the glass, aluminum oxide octahedron [AlO6] is formed in the network gap; when there is enough free oxygen, Al 3+ The non-bridging oxygen is captured to reconnect the network originally disconnected by R2O, so that the structure can be strengthened. An appropriate amount of Al2O3 can reduce the crystallization tendency of glass and improve the chemical stability and mechanical strength of glass. However, excessive introduction will increase the high-temperature viscosity of glass and increase the crystallization tendency of cordierite. The present invention limits the Al2O3 content to 16-21%.

[0026] CaO is a network body, and its coordination number is generally 6. At high temperature, Ca 2+ The accumulation effect is weak, the polarization ability is strong, and the high temperature viscosity of the glass is reduced. CaO can shorten the glass material, which is beneficial to large-scale tank kiln production. However, when Ca 2+ When the content is too high, the glass becomes more brittle. 2+ The ion radius is large, the field strength is small, and the accumulation effect is weak. It mainly provides free oxygen in the glass, reduces the continuity of the silicon-oxygen skeleton, and reduces the elastic modulus of the glass. The present invention limits the CaO content to 0.4-4%.

[0027] MgO is an alkaline earth metal oxide, an inert gas type cation, and acts as a network external oxide in glass. It does not participate in the network, and the strength of the ionic bond is small. 2+ Mg ions in glass can provide free oxygen to reduce the continuity of the silicon-oxygen skeleton and can repair the broken silicon-oxygen network at the original broken bond. 2+ The ion radius is small, the field strength is large, the accumulation effect is stronger, the broken network is accumulated, the glass network structure is more compact, and the elastic modulus of the glass is effectively improved. The present invention limits the MgO content to 13-18%.

[0028] Fe2O3 in the glass network is mainly Fe 2+ and Fe 3+ There are two ionic forms, Fe 2+ It can be used as a network modifier to disconnect some [SiO4] and [AlO4] tetrahedrons, destroy the glass network structure, and reduce the mechanical properties of the glass; while Fe 3+ A triangular pyramidal network structure can be formed, which can enhance the network structure of the glass by aggregation, increase the connection between [SiO4] and [AlO4], and improve the elastic modulus of the glass. 3+ / Fe 2+ The ratio can effectively improve the elastic modulus of glass, but excessive Fe2O3 will affect the thermal permeability of molten glass, which is not conducive to large-scale tank kiln production. The present invention limits the Fe2O3 content to 0.3-0.8%.

[0029] Na2O and K2O are oxides outside the glass. + Residing in the holes of the glass structure network, it can provide free oxygen, reduce the Si / O ratio, and increase the non-bridging oxygen content. The appearance of non-bridging oxygen causes the silicon-oxygen network to break, and its excess charge is neutralized by the alkali metal ions; the silicon-oxygen tetrahedron loses its original integrity and symmetry, making the glass structure loose and the physical properties deteriorate. However, an appropriate amount of Na2O and K2O can effectively reduce the high-temperature resistivity of the glass, which is beneficial to the utilization rate of the electric melting system in large-scale pool kiln production, helps to improve the glass melting quality, and improves the fiberization efficiency of glass fibers. The present invention limits the K2O+Na2O content to ≤0.5%.

[0030] Although Li2O is a network-external oxide like Na2O and K2O, it plays a special role in glass. When Si / O is relatively large, it mainly provides free oxygen, increases the non-bridging oxygen content, has a bond-breaking effect, destroys the integrity of the glass network structure, and has a strong fluxing effect. When Si / O is relatively small, due to Li + Radius ratio K + 、Na +The field strength is larger, which mainly manifests as an accumulation effect, making the glass network structure more compact and effectively reducing the tendency of glass crystallization. However, a large amount of Li2O will increase the tendency of glass crystallization. The present invention limits the content of Li2O to between 0.1 and 0.7%.

[0031] B2O3 is a network former with boron-oxygen triangle [BO3] and boron-oxygen tetrahedron [BO4] as structural units. In borosilicate glass, it forms a structural network with silicon-oxygen tetrahedron. The higher the [BO4] ratio, the stronger the network structure. Adding a small amount of B2O3 can reduce the high-temperature viscosity of the glass, which is conducive to clarification. When the content is too high, the proportion of [BO3] increases, boron anomaly occurs, and the physical properties of the glass deteriorate. The present invention limits the B2O3 content to 0.3~0.8%.

[0032] Y2O3 acts as a network exosome in the glass, providing free oxygen, which reduces the degree of connection between [SiO4] tetrahedra, while Y 3+ The Y2O3 is filled in the network gap and forms [YO7] ligands with non-bridging oxygen, thereby improving the connection degree of the network structure unit of the glass. 3+ Distributed in the gaps of the glass network structure, the glass network structure is tightly connected, and the elastic modulus of the glass is effectively improved. Excessive Y2O3 will aggravate the degree of damage to the network structure. 3+ The effect of making the network structure compact is limited, and the elastic modulus of the glass decreases. The present invention limits the Y2O3 content to 0-2.5%.

[0033] As a strong oxidant, CeO2 can release oxygen at high temperatures, promoting the discharge of bubbles in the glass liquid. CeO2 can effectively replace sodium sulfate Na2SO4 and reduce the Na + The introduction of CeO2 reduces the generation of SO2 gas during glass melting, reduces the corrosion of refractory materials, and reduces the SO2 content in the flue gas discharged by the kiln. The present invention limits the CeO2 content to 0.1-0.5%.

[0034] ZnO generally uses zinc oxide octahedron [ZnO6] as the external oxide of the network. When there is enough free oxygen in the glass, zinc oxide tetrahedron [ZnO4] can be formed and enter the glass network structure, making the glass structure more stable and improving the glass elastic modulus. However, the introduction of ZnO into the glass usually leads to the crystallization of zinc aluminum spinel (ZnAl2O4) and quartz. The melting point of zinc aluminum spinel is 1950℃, which is not easy to melt and will seriously block the nozzle, affecting the wire drawing operation; zinc aluminum spinel will also lead to the enrichment of Cr content in the three-phase interface area, forming chromium magnesium spinel. Quartz crystallization usually floats on the surface of the glass liquid in the working channel. It is extremely difficult to handle after it is generated. At the same time, it will further promote the crystallization tendency of zinc aluminum spinel at the nozzle, seriously affecting the wire drawing operation. In this glass system, due to the low CaO content, the crystallization ability of cordierite is stronger. The present invention introduces ZnO and adjusts the ratio of ZnO to Al2O3, so that zinc aluminum spinel and quartz crystallization will not occur, and the glass component can be deviated from the cordierite central area in the MgO-Al2O3-SiO2 ternary phase diagram at the same time, which increases the activation energy of cordierite crystallization, inhibits the crystallization ability, reduces the crystallization rate, and reduces the cordierite crystallization tendency of the glass to a minimum. In the wire drawing process, even if cordierite crystallization particles appear, due to its low crystallization tendency and large crystallization activation energy, the cordierite crystallization particles cannot grow up rapidly, and the situation of leak plate back climbing or flying wire will not be caused. ZnO, as a high field strength ion, can induce 4-coordinated [AlO4] to change to 5-coordinated [AlO5], and [AlO5] makes the glass network structure more compact by connecting 3-coordinated oxygen Q3, effectively improving the glass elastic modulus. If the amount of ZnO is too much, the glass will be prone to crystallization. The present invention limits the ZnO content to 0.1-4.0%, and limits ZnO / Al2O3 to 0.02-0.35.

[0035] In conventional glass systems, the introduction of B2O3 can effectively reduce the glass density, but the stability of 3-coordinated [BO3] is poor, which will significantly reduce the modulus of glass fiber. The Li2O and ZnO introduced in the present invention both have the effect of inducing the transformation of [BO3] to [BO4], which can effectively improve the fiber modulus. However, excessive Li2O will significantly reduce the surface tension of the glass liquid, which is not conducive to the wire drawing operation, and even cause crystallization and back-stripping; excessive ZnO will cause zinc aluminum spinel and quartz crystallization. In the present invention, by adjusting the ratio of Li2O+ZnO and B2O3, the synergistic effect of Li2O and ZnO is fully utilized, and the transformation of [BO3] to [BO4] is promoted to the greatest extent, while avoiding the occurrence of too low surface tension of the glass liquid, increased crystallization upper limit and boron anomaly, while reducing the glass density and improving the fiber modulus, without causing adverse effects on the wire drawing operation. The present invention defines (Li2O+ZnO) / B2O3≥1.0.

[0036] In the present invention, Al2O3 is introduced by calcining kaolin, and lithium slag waste is used, which inevitably introduces some Fe2O3. Generally, too high Fe2O3 will lead to an increase in the FeO content in the glass, which seriously affects the heat permeability of the glass liquid in the tank kiln and affects the melting quality of the glass liquid. In the present invention, an appropriate amount of CeO2 is introduced to promote Fe2O3 through its strong oxidizing property. 2+ Fe 3+ The change can effectively improve the thermal permeability of glass liquid, which is beneficial to large-scale tank kiln production. On the other hand, the FeO content is reduced, and Fe 3+ / Fe 2+ The ratio increases, and CeO2 can induce Fe 2+ Fe 3+ Transformation, increase Fe 3+ The increase of the content increases the connection degree between [SiO4] and [AlO4], which can effectively improve the elastic modulus of glass. The present invention stipulates that CeO2 / Fe2O3≥0.3.

[0037] The density of the glass of the present invention is affected by the molar mass of the glass oxide composition and its internal structure. The molar mass of ZnO and Y2O3 is relatively large, and the Y 3+ The ions have a high field strength effect, which makes the glass structure compact and significantly improves the glass density. The present invention limits Y2O3+ZnO to 1.0-5.0%.

[0038] The beneficial effects of the present invention are as follows:

[0039] In order to reduce production costs, the Al2O3 of the present invention is introduced by calcined kaolin and lithium slag waste is used. However, the introduced Fe2O3 is usually used as a harmful element impurity that affects the thermal permeability of glass in conventional high modulus formulas. The present invention introduces an appropriate amount of CeO2 to promote Fe 2+ Fe 3+ Transformation, increase Fe 3+ / Fe 2+ ratio, effectively improving the elastic modulus of glass.

[0040] The invention promotes the transformation of [BO3] to [BO4] by introducing appropriate amounts of Li2O and ZnO, thereby effectively reducing the glass density and improving the elastic modulus of the glass fiber.

[0041] The present invention introduces an appropriate amount of Li into the SiO2, Al2O3, CaO, MgO glass system. 2+ , Y 3+ This type of high-field strength ions can give full play to their accumulation effect, compact the glass network structure, improve the elastic modulus, while increasing the crystallization activation energy of the glass system, increasing the crystallization barrier, reducing the glass crystallization tendency, and lowering the glass liquidus temperature, which is beneficial to large-scale pool kiln production.

[0042] In the prior art, in order to improve the elastic modulus of glass, a large amount of Al2O3 and MgO are introduced, while the CaO content is reduced, which makes the glass fiber cordierite crystallization tendency extremely strong, which is not conducive to large-scale tank kiln production. 2+ It captures the free oxygen provided by R2O and RO in the glass to form zinc oxygen tetrahedron [ZnO4], reconnecting the network structure originally disconnected by R2O, thereby strengthening the glass network structure and improving the glass elastic modulus; on the other hand, ZnO increases the crystallization tendency of zinc aluminum spinel and quartz, causing the glass component to deviate from the cordierite phase center of the MgO-Al2O3-SiO2 ternary phase diagram, while inhibiting the crystallization of cordierite, and avoiding the appearance of zinc aluminum spinel and quartz crystal particles near the liquidus temperature.

[0043] When an appropriate amount of ZnO is introduced into the present invention, it is found that Zn 2+ It can induce the transformation of 4-coordinated [AlO4] to 5-coordinated [AlO5]. [AlO5] connects 3-coordinated oxygen Q3, making the glass network structure more compact and effectively improving the glass elastic modulus. The present invention maximizes the effect of Al2O3 on improving the modulus in glass fiber by adjusting the ratio of ZnO to Al2O3.

[0044] The present invention controls the introduction of elements with larger molar mass to obtain a density of ≤2.61 g / cm 3 By controlling the proportion of elements, reducing the proportion of non-bridging oxygen in the glass, and strengthening the glass network structure, the elastic modulus of the glass fiber composition is ≥98.7GPa, and the specific modulus is ≥3.80×10 6 m.

[0045] The glass fiber composition suitable for large wind turbine blades provided by the present invention has a molding temperature between 1280 and 1330°C, a liquidus temperature of the glass fiber provided by the present invention does not exceed 1310°C, and a difference between the molding temperature and the liquidus temperature △T>0°C. By adjusting the crystallization type, crystallization rate, crystallization activation energy and preparation process, even if the operating window temperature △T is small, the glass fiber composition will not produce crystallization during the production process, meets the wire drawing process requirements, and can be mass-produced in large-scale pool kilns. DETAILED DESCRIPTION

[0046] The present invention is specifically described and illustrated below in conjunction with embodiments.

[0047] The present invention is applicable to a production process of a glass fiber composition for large wind turbine blades, comprising the following steps:

[0048] (1) Calculate the mass of various raw materials required according to the content of each component, weigh each raw material, mix them evenly by pneumatic force, and then transport them to the kiln head silo to obtain the batch material, and then use the feeder to feed the batch material into the large tank kiln at a uniform speed;

[0049] (2) The mixed batch is melted at 1450-1550°C in a tank kiln and clarified into a homogeneous glass liquid;

[0050] (3) The glass liquid is drawn through the nozzle on the platinum-rhodium leak plate at 1280-1330°C to form glass fiber;

[0051] (4) The glass fiber passes through an oil coating device, is coated with a wetting agent, is pulled around a wire drawing machine, and is drawn into a raw fiber product.

[0052] The present invention also provides a production process for a glass fiber composition suitable for large wind turbine blades, which reduces the leakage plate back-climbing condition, prolongs the leakage plate life, and improves the glass fiber production efficiency by improving the leakage plate and wire drawing process.

[0053] The operating window temperature △T of the present invention is relatively small. In order to meet the requirements of the wire drawing process and realize large-scale pool kiln production, the bushing and wire drawing process are modified as follows:

[0054] (1) The diameter of the nozzle was reduced from 1.8 mm to 1.3 mm, and the nozzle length was extended from 3.2 mm to 3.6 mm to suppress the crystallization tendency of the glass liquid at the nozzle and improve the glass liquid back-climbing phenomenon during the wire drawing process;

[0055] (2) In order to cool the glass liquid quickly after it is wired and avoid the formation of crystallization particles, the air conditioning wind speed is increased from the original 15m / s to 22m / s. At the same time, the original solid cooling fins are replaced with hollow water-cooled cooling fins to enhance the cooling capacity of the leak plate and shorten the cooling time after the glass fiber is formed, which is conducive to inhibiting the formation of crystallization particles during the wire drawing process and improving production efficiency;

[0056] (3) The small hole diameter of the leak plate, the long leak nozzle length and the high leak plate temperature will inevitably lead to deformation and damage of the leak plate, especially the electrode is prone to cracking and seepage. By thickening the electrode from the original 5mm to 10mm and using leak plate reinforcement ribs, the high temperature deformation and damage of the leak plate can be effectively slowed down and the life of the leak plate can be extended.

[0057] When verifying the comprehensive performance of the glass fibers in the embodiments and comparative examples, the following parameters were selected:

[0058] 1) Molding temperature, that is, the temperature at which the viscosity of the glass is 1000 Poise, can characterize the molding temperature of the fiber. The high-temperature viscosity of the glass can be obtained using a high-temperature viscometer.

[0059] 2) Liquidus temperature, that is, the critical temperature at which the glass begins to crystallize, is generally the upper limit of the glass crystallization temperature. The upper limit of the glass crystallization temperature is obtained using a crystallization furnace.

[0060] 3) ΔT, the difference between the molding temperature and the liquidus temperature.

[0061] 4) Crystallization type: tested by X-ray diffractometer.

[0062] 5) Crystallization particle state: Use polarizing microscope. Unit area (1mm 2 ) Grain quantity assessment levels: dense (>15), medium (5-15), small (<5); grain size assessment levels: large (>50μm), medium (20-50μm), small (<20μm).

[0063] 6) Glass density is tested according to ASTM C693 standard test method for glass density by buoyancy method.

[0064] 7) Elastic modulus is tested according to ASTM D2343 standard.

[0065] 8) Specific modulus is the ratio of the elastic modulus to the density of the material: Specific modulus = elastic modulus / (density × 9.8) Unit: 10 6 m.

[0066] Examples 1-8

[0067] The contents and performance indicators of the glass fiber compositions of Examples 1-8 are shown in Table 1.

[0068]

[0069] Comparative Examples 1-6

[0070] The contents and performance indicators of the glass fiber compositions of Comparative Examples 1-6 are shown in Table 2.

[0071]

[0072] The glass fiber compositions of Examples 1-8 and Comparative Examples 1-6 inevitably contain impurities, and the remainder in the formula amount is the content of the impurities.

[0073] From the above, it can be seen that Examples 1-8 promote the transformation of [BO3] to [BO4] by introducing appropriate amounts of Li2O and ZnO, which effectively reduces the glass density and increases the elastic modulus of the glass fiber.

[0074] In Comparative Examples 1-3, since any one of Li2O, ZnO, and B2O3 is missing, it is difficult to realize pool kiln production.

[0075] In Comparative Examples 4-5, the mass percentages of ZnO and Al2O3 are 0.015 and 0.4 respectively, which are not in the range of ZnO / Al2O3=0.02~0.35, resulting in poor effects and difficulty in achieving pool kiln production.

[0076] In Comparative Example 6, the mass percentage content of Li2O+ZnO and B2O3 does not satisfy (Li2O+ZnO) / B2O3≥1.0, and is only 0.83. The effect is also poor, and it is difficult to achieve pool kiln production.

[0077] In summary, Comparative Examples 1-6 cannot achieve the purpose of the present invention, while Examples 1-8 obtain a density of ≤2.61 g / cm 3 By controlling the ratio of elements and strengthening the glass network structure, the elastic modulus of the glass fiber is ≥98.7GPa and the specific modulus is ≥3.80×10 6 m.

Claims

1. A glass fiber composition suitable for large wind turbine blades, characterized in that: In terms of mass percentage, the content of each component is as follows: SiO2: 57~62%, Al2O3: 16~21%, CaO: 0.4~4%, MgO: 13~18%, Fe2O3: 0.3~0.8%, Li2O: 0.1~0.7%, Y2O3: 0~2.5%, ZnO: 0.1~4.0%, B2O3: 0.3~0.8%, CeO2: 0.1~0.5%, K2O+Na2O≤0.5%, the remainder is impurities; The mass percentage of ZnO and Al2O3 satisfies ZnO / Al2O3=0.02~0.35; the mass percentage content of Li2O+ZnO and B2O3 satisfies (Li2O+ZnO) / B2O3≥1.0; the mass percentage content of CeO2 and Fe2O3 satisfies CeO2 / Fe2O3≥0.

3.

2. The glass fiber composition suitable for large wind turbine blades according to claim 1, characterized in that: The mass percentage content of Y2O3 and ZnO satisfies Y2O3+ZnO: 1.0~5.0%.

3. The glass fiber composition suitable for large wind turbine blades according to claim 1, characterized in that: The density of glass fiber composites suitable for large wind turbine blades is ≤2.61g / cm 3 .

4. A glass fiber made of the glass fiber composition suitable for large wind turbine blades according to any one of claims 1 to 3, characterized in that: The molding temperature of glass fiber is 1280~1330℃.

5. The glass fiber made of the glass fiber composition suitable for large wind turbine blades according to claim 4, characterized in that: The specific modulus of glass fiber is ≥3.80×10 6 m.

6. The glass fiber made of the glass fiber composition suitable for large wind turbine blades according to claim 4, characterized in that: The elastic modulus of glass fiber is ≥98.7GPa.

7. The glass fiber made of the glass fiber composition suitable for large wind turbine blades according to claim 4, characterized in that: The liquidus temperature of glass fiber is ≤1310℃.

Citation Information

Patent Citations

  • High- modulus glass composition, high -modulus glass fiber and composite material

    CN113929299A

  • High-magnesium high-specific modulus glass fiber composition and glass fiber

    CN116282934A

  • High-performance heat- and corrosion-resistant glass fiber composition

    CN102276153A

  • Glass fiber and composition for glass fiber

    JP7235928B1